Modeling and Simulation of Cuttlefish-imitating Underwater Sampling Manipulators - Zhang Xuehai; Yang Zehui; Wang Rugui; Zeng Qineng (Jixie chuandong)
In order to solve the problem of sample damage caused by excessive pressure exerted by the manipulator during underwater operation and the problem that sample cannot be saved after grasping, this study designs an underwater sampling manipulator driven by two coupling cylinder drivers that imitates the eating mode of acuttlefish. There is a bias impeller pump inside the manipulator, which forms a low pressure area to drive the water flow to draw the samples that are difficult to collect without contact. The three-dimensional model of the manipulator is established and the kinematics equation of the manipulator is calculated. The functional relation between the driver and the end effector is solved by the closed-loop vector method. The workspace and trajectory planning are obtained, and the rationality and feasibility of the manipulator structure are verified. Finally, the manipulator is assembled on the underwater robot, and the underwater navigation sampling at different angles is simulated, which lays a certain foundation for the future research of the manipulator in visual control and grasping.